Anti-cancer potential of non-curcuminoid bioactive from Curcuma caesia Roxb. (Black Turmeric): Targeting cervical cancer via PI3K/Akt pathway modulation - Bishnu P. Parida; Megha Radhakrishnan; Varsha Goyal; Astha Sharma; Rupesh Zarekar; Mumtaz A. Ansari; Jasmeet Singh; Sunita Singh; Gopeshwar Narayan (European Journal of Medicinal Chemistry Reports)
Curcuma caesia, or black turmeric, is a significant medicinal plant used in traditional Indian medicine, including Ayurveda and folk practices. Indigenous communities in the northern Indo-Gangetic plains have utilized it for its analgesic, anti-inflammatory, and anti-infective properties. However, the anti-cancer potential of non-curcuminoid bioactive from Curcuma caesia remains underexplored. The current study investigates the anti-cancer potential of non-curcuminoid bioactive compounds derived from Curcuma caesia rhizome extracts, focusing on their effects against cervical cancer.Using high-resolution mass spectrometry (HRMS), key compounds were identified from hexane (HECC) and methanolic (MECC) extracts, among which 3,4-dihydrocoumarin and (+)-ar-turmerone were prominent. In vitro cytotoxicity assays demonstrated that both HECC and MECC selectively inhibited the viability of cervical cancer cell lines, sparing non-tumorigenic HEK293T cells. Mechanistic analyses revealed that 3,4-dihydrocoumarin treatment led to mitochondrial membrane hyperpolarization, suppression of intracellular ROS, and cell cycle arrest at subG1 and G1 phases, while (+)-ar-turmerone had antagonistic modulatory effects. Western blotting confirmed downregulation of PI3K and Akt protein expression. Complementary ADME profiling indicated favorable pharmacokinetic properties, while molecular docking supported strong binding affinity of 3,4-dihydrocoumarin to PI3K and Akt targets, reinforcing its mechanism of action.Curcuma caesia rhizome fractions, especially 3,4-dihydrocoumarin, exhibit anti-cancer properties by modulating key molecular pathways, including the PI3K/Akt pathway.